The Curious Why - DiTerlizzi, Angela; Alvarez, Lorena (New York : Little, Brown and Company, 2024)
A magical friend called the Curious Why encourages childrens imaginations to fly, as they consider "how, what, where and when?" in relation to the world around them.
Ages 4-8.
Keywords: Curiosity -- Juvenile fiction; Information behavior -- Juvenile fiction; Imagination -- Juvenile fiction; Curiosity -- Fiction; Information retrieval -- Fiction; Imagination -- Fiction; Stories in rhyme; Picture books